Numerical and Experimental Investigation of the Seismic Performance of Steel Concentrically Braced Frame Structures - HICKEY, JOHN MICHAEL (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2019)
The concepts of performance-based earthquake engineering (PBEE) and performance based seismic design (PBSD) emerged after the 1994 Northridge and 1995 Kobe earthquakes, where the level of damage to structures, economic loss due to loss of use and cost of repair were unexpectedly high. PBSD involves achieving stated performance objectives when a structure is subjected to a particular level of seismic hazard. In order to allow PBSD to be implemented, performance assessment procedures have been developed and refined through the work of Pacific Earthquake Engineering Research (PEER) centre and the FEMA P-58 research project. Steel Concentrically Braced Frames (CBFs) are stiff, lightweight, potentially low-cost structures that efficiently resist lateral load through diagonal bracing members. Under dissipative seismic design principles, these bracing members are allowed to behave inelastically during infrequent high-intensity earthquakes. Recent earthquakes have shown that steel frame structures designed to modern codes are unlikely to collapse even under very severe seismic loads. However significant damage, and subsequent losses, can be incurred by both structural and particularly non-structural building components, highlighting the need for PBSD-type procedures. This is particularly important for CBFs, where the high inherent stiffness, and the resulting difficulty in coordinating structural and non-structural response, makes achieving adequate performance challenging. Therefore, this thesis investigates the lifetime seismic performance, and examines methods to improve performance assessment, for CBFs designed to Eurocode 8. The impact of decisions taken at the design stage on performance of CBFs designed to Eurocode 8 is assessed. This is done by using the FEMA P-58 performance assessment methodology to calculate lifetime losses suffered by a set of CBFs designed using different behaviour factors to vary frame stiffness and strength. Expected losses are shown to increase with the behaviour factor and seismic hazard. The results of the work suggest that the designer has the ability to limit drift dependant losses to by increasing frame stiffness, but that acceleration dependant losses are more difficult to control. A so-called ?rapid? performance assessment methodology specifically for CBFs designed to Eurocode 8 was proposed. This is based on the development of methods to predict response parameters of interest based on nonlinear static analysis. This avoids the need to carry out computationally intensive nonlinear time history analyses (NLTHA), thus allowing for more practicable application of performance assessment methodologies. Similar values for performance measures were obtained from the ?rapid? method developed here and from conventional NLTHA-based performance assessment. The calculation of performance measures like expected repair costs or downtime is based on the ability to accurately predict response parameters of interest for various earthquake scenarios. However, this is challenging for CBFs, where response can be highly nonlinear and difficult to model correctly. In order to assess model accuracy, an experimental substructured hybrid simulation testing programme examining the response of a three storey CBF structure was undertaken. A novel model updating algorithm to optimize modelling parameters was developed and validated. This was applied to the results of the hybrid simulations. The primary conclusion from this process was that the numerical models employed appear to overestimate the stiffness of CBF structures, something which can be improved by reducing the elastic modulus. This was supported by analysis of the results of shaking table tests from a previous research project. The conclusions of the performance assessment previously carried out were reassessed in this context. It was demonstrated that the calculation of performance measures is quite robust and reasonably insensitive to modelling assumptions or error.
APPROVED
Keywords: Earthquake Engineering, Concentrically Braced Frame, Eurocode 8, Steel Structures, Seismic Performance Assessment, Hybrid Simulation